Arsenic, antimony, and Leishmania: has arsenic contamination of drinking water in India led to treatment- resistant kala-azar?. (26th February 2015) - Perry, Meghan; Wyllie, Susan; Prajapati, Vijay; Menten, Joris; Raab, Andrea; Feldmann, Joerg; Chakraborti, Dipankar; Sundar, Shyam; Boelaert, Marleen; Picado, Albert; Fairlamb, Alan
Abstract: Background: In Bihar state, India, the cure rate of antimonial compounds (eg, sodium stibogluconate) in the treatment of visceral leishmaniasis (VL) has fallen from more than 85% to less than 50%. This reduction has been attributed to long-term, widespread misuse of antimonial drugs within the Indian private health-care system. We aimed to test the hypothesis that exposure to arsenic in drinking water in this region has resulted in antimony-resistant Leishmania parasites. Methods: L donovani parasites were serially passaged in mice exposed to environmentally relevant concentrations of arsenic in drinking water. Arsenic concentrations in murine organs were quantified and the sensitivity of L donovani to sodium stibogluconate assessed at each passage. A retrospective field study on a cohort of antimony-treated patients with VL was performed in an arsenic-contaminated area of Bihar to assess risk of treatment failure and death in people exposed to arsenic. Findings: Arsenic accumulation in organs of exposed mice was proportional to exposure level. After five passages, isolated parasites were refractory to sodium stibogluconate in in-vitro drug sensitivity assays. Treatment of arsenic exposed, infected mice with this drug confirmed that these parasites retained resistance in vivo. In the field work study, 110 patients with VL treated with sodium stibogluconate, failure rate was 59%. Patients using well water with high mean arsenic concentrations had a higher risk of treatment failure than patients using wells with arsenic levels of less than 10 μg/L (odds ratio 1·78, 95% CI 0·7–4·6, p=0·23). 21 patients died, 16 directly as a result of their disease. Mean arsenic concentrations of more than 10 μg/L increased the risk of all-cause and VL-related mortality (hazard ratio 3·27, 95% CI 1·4–8·1, and 2·65, 0·96–7·65, respectively). Interpretation: These data suggest that arsenic contamination might have contributed to the development of antimonial resistance in Leishmania parasites in Bihar. Our epidemiological study was underpowered and retrospective in nature, so firm conclusions cannot be made. Further research into the associations between arsenic exposure and antimonial treatment failure and death in the leishmaniases is warranted. Funding: Wellcome Trust.